Effect of Sesame Oil on Lipid Profile and Liver Enzymes in Male Albino Rats Treated With Carbone Tetrachloride (CCl4) - Abdul-Lattif, Rashaa Faiq (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
This study was designed to investigate the effect of sesame oil on lipid profile and liver enzyme in male albino rats treated with Carbone tetrachloride (CCl4).    Forty adult male rats were divided into four equal groups, first group was daily administrated with tap water, the second group was injected with CCl4 (80mg/kg.BW/day), the third group was administrated with sesame oil (150mg/kg.BW/day) and the fourth group was injected with CCl4 (80mg/kg.BW/day) and was administrated with sesame oil (150 mg /kg.BW /day) for 30 days. The statistical  results of the present study showed a significant  (p